Certolizumab Pegol for the Treatment of Plaque Psoriasis in Routine Clinical Practice: One-Year Results from the CIMREAL Study - Bernhard Korge; Olivier Vanhooteghem; Charles W. Lynde; Alena Machovcova; Marc Perrussel; Elisavet Lazaridou; Claudio Marasca; David Vidal Sarro; Ines Duenas Pousa; Frederik Fierens; Paulette Williams; Saori Shimizu; et al. (Adis, Springer Healthcare, 2024)
Abstract Introduction Certolizumab pegol (CZP) is an anti-tumor necrosis factor alpha (TNFα) approved for the treatment of moderate to severe plaque psoriasis (PSO). However, data on its real-world use is currently limited. The objective of this study was to describe the 1-year real-world effectiveness of CZP, its impact on health-related quality of life (HRQoL), and safety outcomes in patients with moderate to severe PSO in multi-country settings. Methods CIMREAL, a prospective, noninterventional study, was conducted across Europe and Canada from August 2019 to December 2022. Patients were followed for 1-year, receiving CZP 400 mg initial doses at weeks 0, 2, and 4, followed by CZP 200 mg every 2 weeks (Q2W) or CZP 400 mg Q2W maintenance dosing. Effectiveness was assessed using the Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI). Safety was also evaluated. Results Overall, 399 patients with moderate to severe PSO were included. Of these, 93.7% (374/399) and 77.9% (311/399) completed months 3 and 12, respectively. Mean age (± standard deviation) was 42.9 ± 13.5 years and body mass index was 28.5 ± 6.8 kg/m2, with the majority of patients being female (68.2%). At 12 months, CZP showed substantial effectiveness, achieving PASI 75 and PASI 90 response rates (≥ 75% and ≥ 90% improvement from baseline, respectively) of 77% and 56.5%, respectively. Patients with PASI score of ≤ 3 and ≤ 2 experienced improvement from 3 months (49.8% and 41.1%, respectively) to 12 months (82.0% and 75.3%, respectively). HRQoL considerably improved, with mean DLQI scores decreasing from 12.4 to 2.3 after 12 months of treatment, and the proportion of patients with DLQI 0/1 increased from 28.6% at 3 months to 59.4% at 12 months. The 1-year probability of persistence was approximately 85%. Overall, 30.6% of the patients experienced any adverse events and 9.3% had serious adverse events. Conclusion In routine clinical practice, CZP exhibited consistent effectiveness, positively impacting both skin psoriasis activity and HRQoL. The 1-year persistence of CZP was high, and no new safety signals were identified. Trial Registration Number ClinicalTrials.gov Identifier: NCT04053881 https://www.clinicaltrials.gov/study/NCT04053881 .